Vigor Enhancement of Tomato (Solanum lycopersicum) using Spirulina platensis as Seed Priming Agent - Pratiwi, Indah Wahyu; Rahmawati, Fitri Ayu; Samtani, Kariena; Atuilah, Nuning; Hidayatullah, Reza Aris; Alfiah, Nur Aini; Wilujeng, Elly Daru Ika; Anindita, Devina Cinantya; Shidiqi, Moh Hasbi Ash; Adnan, Moch. Rosyadi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Seed priming is a technique to enhance seed germination. Biopriming, a specific method, involves soaking seeds in biological agents such as Spirulina platensis, a microalga that can thrive in agricultural waste including Sugar Mill Effluent (SME). Spirulina sp. contains various beneficial growth hormones, making it a potential seed priming agent. This research aimed to determine the effectiveness of tomato seed priming using Spirulina platensis grown on SME. The research was conducted from May to August 2024 at the Seed Technology Laboratory, Politeknik Negeri Jember. The research method used a factorial Completely Randomized Design which included Spirulina platensis biomass concentrations (0, 30, 45, and 60%) and soaking durations (1, 2, and 3 hours). Analysis of variance using the Bonferroni post-hoc test at a 5% level using GraphPad Prism version 5.01. The results showed that seed priming with S. platensis positively influenced several physiological parameters, including mean germination time, vigor index, seed growth rate, and shoot length. These findings demonstrated that SME-grown S. platensis cells capable of improving the physiological quality of tomato seeds, making it one of the environmentally friendly seed invigorating techniques.